The Influence of LPG Fuelling on Diesel Engine Cycle Variability. (2016) - Cernat, Alexandru; Pana, Constantin; Negurescu, Niculae; Nutu, Cristian
Abstract: Liquid Petroleum Gas physic-chemical properties lead to specific aspects of the in-cylinder combustion and mechanical running of diesel engines. Comparative to the classic diesel engine, the cycle variability coefficients (COV) are presented at dual fuelling for maximum pressure, maximum pressure rise rate, maximum pressure angle, indicated mean effective pressure, heat release rate and cycle angle points of mass fraction burned. The calculated values of these parameters are bigger comparative to the normal values of diesel engines, but don't exceed the maximum admitted values that provide engine reliability. From COV values analysis, the maximum admitted LPG cycle dose is also established.